2023
DOI: 10.1057/s41599-022-01499-5
|View full text |Cite
|
Sign up to set email alerts
|

Do personal values and motivation affect women’s solo travel intentions in Taiwan?

Abstract: Female solo travel is experiencing a global increase and specifically, gaining popularity in Asia. This study explores how personal values and female solo travel motivation affect travel behavior. Using a sample comprising 381 single females in Taiwan, partial least squares structural equation modeling was utilized to investigate the hypotheses. The results revealed Hypothesis 1 and Hypothesis 3 are supported, which verifies personal internal values significantly affect female solo travel motivation, and are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
1
0
1
1
Order By: Relevance
“…This also agrees with the findings of Sangpikul (2009), discovering that the most perceived push dimensions to push Asians and Europeans to Thailand were novelty-seeking and escape and relaxation. This is similar to the results of Chen et al (2023) study andTeng et al (2023) study. Based on the above, this research will concentrate on the following push dimensions mentioned by Yousefi and Marzuki (2015), namely rest and relaxation, enhancing the ego, and novelty and knowledge seeking.…”
Section: Literature Reviewsupporting
confidence: 93%
See 1 more Smart Citation
“…This also agrees with the findings of Sangpikul (2009), discovering that the most perceived push dimensions to push Asians and Europeans to Thailand were novelty-seeking and escape and relaxation. This is similar to the results of Chen et al (2023) study andTeng et al (2023) study. Based on the above, this research will concentrate on the following push dimensions mentioned by Yousefi and Marzuki (2015), namely rest and relaxation, enhancing the ego, and novelty and knowledge seeking.…”
Section: Literature Reviewsupporting
confidence: 93%
“…However, different results were found regarding the last push dimension, which is the rest and relaxation. The findings of this research regarding the impact of rest and relaxation on internal tourists' visit intention to a domestic destination in Egypt (H1-1) was insignificant, and accordingly showed inconsistency with the results of Chen et al (2023), Teng et al (2023), andSangpikul (2009), who argued that escape and relaxation have a positive significant impact on the visit intention as per the study of each. Therefore, H1-2 and H1-3 were met.…”
Section: Discussioncontrasting
confidence: 75%
“…The results of this study are consistent with previous research conducted by Chu (2018), Li and Cai (2012), and Teng et al (2023) who found a positive relationship between visitor motivation and visit intention. However, this study differs from previous research conducted by Suhud and Allan (2019) and Suhud and Wilson (2016), who suggested a connection between motivation and the stage of readiness in other contexts.…”
Section: Discussionsupporting
confidence: 92%
“…Por una parte, se ha visto una tendencia teórica a considerar a las mujeres que viajan solas como sujetos en búsqueda de autorrealización, puesto que mientras realizan actividades turísticas en solitario serían capaces de separarse de sus roles sociales preestablecidos para buscar una identidad propia y un autodesarrollo (Leves-Maneze y Boscolo-Pacheco, 2019; Neluhena et al, 2023;A. Pereira y Silva, 2018;Teng et al, 2023). Por otra parte, también se consideran como factores de autorrealización las motivaciones vinculadas a la religiosidad y a la espiritualidad (Ivtzan et al, 2013; Koltko-ROTUR, Revista de Ocio y Turismo Rivera, 2006;Watson et al, 1995).…”
Section: Marco Teóricounclassified